Valorización de opciones reales: modelo Ornstein-Uhlenbeck - Tresierra Tanaka, Álvaro (2016)
This study has as its main objective to develop an analysis of decision making under uncertainty using the real options application in the evaluation of investments in mining projects. It is also proposed to study the behaviour of gold prices, for the specific case of Peru, using historic prices and based on the commodity prices process. The Ornstein-Uhlenbeck model has been used for this. The main result is that to evaluate projects using the real options approach allows to evaluate –in their real magnitude– the financial benefits associated with an investment project, as it takes into account the trinomial of profitability-risk-flexibility. The assessment method using real options makes it possible to structure strategic thinking.